Contextual Teaching and Learning (CTL) Approaches in Teaching English Writing - Maysuroh, Siti; Agustina, Yulia; Surayya, Siti Ayu; Astuti, Maeli (Journal of English Language and Education, 2025)
Writing is one of the most challenging skills for junior high school students, who often face difficulties in generating ideas, organizing them into coherent paragraphs, and applying correct grammar and vocabulary. Contextual Teaching and Learning (CTL) offers an alternative approach by linking classroom instruction with students’ real-life experiences, thus creating more meaningful and engaging learning activities. This study aims to analyze the implementation of CTL in teaching English writing, to identify the challenges encountered, and to explore the strategies used to overcome them. The research was conducted at SMPN SATAP 2 Aikmel with 15 seventh-grade students, consisting of 8 females and 7 males, who were selected through purposive sampling. A qualitative descriptive design was employed, with data collected through classroom observation, interviews, and documentation of students’ writing products. The findings indicate that the teacher applied CTL principles such as constructivism, inquiry, modeling, collaboration, reflection, and authentic assessment in teaching recount and descriptive texts. Students responded positively, showing greater motivation and confidence when writing tasks were connected to their personal experiences. However, challenges such as limited vocabulary, grammar weaknesses, and time constraints still emerged. To address these, the teacher implemented scaffolding, modeling, peer collaboration, and authentic tasks, which helped students improve both writing skills and motivation. Overall, the study confirms that CTL is an effective framework for enhancing students’ writing ability and engagement in English learning.